IN VITRO STUDY OF THE ANTIMICROBIAL ACTIVITY OF HONEY AGAINST ESCHERICHIA COLI AND ITS POTENTIAL TO SUPPORT THE GROWTH OF LACTOBACILLUS ACIDOPHILUS - Marlin Cindy Claudya Malelak; Agnesia Endang Tri Hastuti Wahyuni; Mariana Reslinda Putri; Christin Melkianus; Aletha Yuliana Mandala; Yunita Apriana Milla; Yohanes Timbun Raja Mangiut Ronael Simarmata (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Antibiotics are widely used in livestock production to promote growth, improve productivity, and prevent disease. However, the continuous use of antibiotics as Antibiotic Growth Promoters (AGPs) may lead to several adverse effects, including the development of antimicrobial resistance, accumulation of antibiotic residues in animal products and the environment, and disruption of beneficial intestinal microflora. Therefore, natural alternatives are increasingly being explored, with honey emerging as a promising candidate. This study aimed to evaluate the antibacterial activity of honey against Escherichia coli and its potential to stimulate the growth of the lactic acid bacterium Lactobacillus acidophilus. Three types of 100% pure honey were tested: Kupang honey, Lombok honey, and commercial honey. Antibacterial activity against E. coli (1.5 × 10⁸ CFU/mL) was assessed using the Kirby–Bauer disc diffusion method, while the effect on L. acidophilus (1.5 × 10⁸ CFU/mL) was evaluated using a modified agar disc diffusion assay for growth stimulation. The results showed that all honey types exhibited antibacterial activity against E. coli, although with relatively small inhibition zones. Lombok honey produced the largest inhibition zone (6.85 mm), followed by Kupang honey (6.26 mm) and commercial honey (6.25 mm). In contrast, all honey samples significantly stimulated the growth of L. acidophilus, as indicated by prominent growth-stimulation zones. Lombok honey showed the largest stimulation zone (26.97 mm), followed by commercial honey (26.88 mm) and Kupang honey (26.66 mm). These findings indicate that the tested honeys possess selective antibacterial activity against E. coli while also promoting the growth of beneficial bacteria. Therefore, honey has strong potential as a natural and sustainable alternative to conventional AGPs for supporting animal health.